TYPES OF MODERN FEDERATIONS: DESCRIPTION AND FEATURES OF APPLICATION - Стогова, О.В. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2012)
The concept and modern types of federalism are explored in the article. The author analyzes main approaches to federations and criterions of their typology. Attention is focused on the types of federations and their characteristics in the modern world. The author made the conclusion that the type of federation should conform to the ethnic composition of population and settlement peculiarities.